2000
DOI: 10.3758/bf03213808
|View full text |Cite
|
Sign up to set email alerts
|

The initial segment strategy: A heuristic for route selection

Abstract: People often choose one route when traveling from point A to point B and a different route when traveling from point B to point A. To explain these route asymmetries, we propose that people rely on a heuristic (the initial segment strategy, or ISS) during route planning. This heuristic involves basing decisions disproportionately on the straightness of the initial segments of the routes. Asymmetries arise because the characteristics that favor selection of a particular route in one direction will usually diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
106
0
2

Year Published

2002
2002
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(134 citation statements)
references
References 19 publications
(11 reference statements)
12
106
0
2
Order By: Relevance
“…However, unlike these works, the predominant factor behind this difference might be not related to the way in which people perceive distance (and therefore act) accordingly, as proposed by Conroy-Dalton (2003) and Bailenson, Shum and Uttal (2000), but to the fact that people seem to have problems in recalling the location of their vehicles due to the homogeneous and featureless nature of parking lots.…”
Section: -Discussionmentioning
confidence: 93%
“…However, unlike these works, the predominant factor behind this difference might be not related to the way in which people perceive distance (and therefore act) accordingly, as proposed by Conroy-Dalton (2003) and Bailenson, Shum and Uttal (2000), but to the fact that people seem to have problems in recalling the location of their vehicles due to the homogeneous and featureless nature of parking lots.…”
Section: -Discussionmentioning
confidence: 93%
“…This suggests that participants' gaze behavior reflects the significance of long lines of sight for their path choices. While related strategies have been demonstrated in other navigation and route selection studies (e.g., Golledge, 1995;Bailenson, Shum, & Uttal, 2000;Conroy Dalton, 2003), it remains unclear why participants chose the option with the longest line of sight. A possible explanation is that this path option promises greater information gain when traveling along than the alternative (Zetzsche et al, 2009).…”
Section: Discussionmentioning
confidence: 97%
“…The results of previous single-destination studies also showed that navigators prefer those routes that begin in the direction of their goal (Golledge, 1995). This least-angle bias has been demonstrated for route choices in small-scale environments (e.g., Bailenson et al, 1998Bailenson et al, , 2000 and in large-scale environments (e.g., Dalton, 2003). The current results are important because they confirm that there may be a common mechanism for route preferences regardless of the size of the space (e.g., Hicheur, Pham, Arechavaleta, Laumond, & Berthoz, 2007;Waller & Nadel, 2013); in this case, the common mechanism is the least-angle bias.…”
Section: Discussionmentioning
confidence: 83%
“…Participants tend to choose a path that has a long initial segment or the fewest turns (Bailenson, Shum, & Uttal, 1998, Bailenson, Shum, & Uttal, 2000Christenfeld, 1995), and, most often, deviate the least from a straight line from start to destination (least angle; Hochmair & Karlsson, 2005). In each case, participants seem to prefer the routes that require the least cognitive effort, even if the path is longer in the end (Wiener, Ehbauer, & Mallot, 2009).…”
Section: Cognitive Biases At Different Environmental Scalesmentioning
confidence: 99%